Correlations of Nitrogen, Phosphorus, Potassium, Pigments and Total Flavonoids of Moringa oleifera Lam. Leaves in the Vegetative and Generative Phases - Rasmani, Rasmani; Aziz, Sandra Arifin; Suketi, Ketty (Department of Agronomy and Horticulture, IPB University, 2020)
Moringa oleifera is universally known as the miracle plant or the tree of life. Moringa leaf extract contains phenolic acids and flavonoids, especially flavonols (quercetin, kaempferol, isorhamnetin glycosides) and flavones (apigenin). This study aimed to elucidate any correlations between nutrient, pigment, and flavonoid concentrations for different leaf positions and different growth phases. The results showed that pigment and total flavonoid concentrations increased from the 1st leaf to the 5th leaf, while nutrient concentration decreased. Pigment concentration, total flavonoid, and nutrient concentration were higher in the vegetative phase than the generative phase. The concentration of nutrients in the generative plants displayed a significant positive correlation with chlorophyll concentration. The 1st to 5th leaf of the vegetative plants can be used as indicator leaves for tissue analysis of the moringa plant.